2017
DOI: 10.1016/j.techfore.2016.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Embedding real options in scenario planning: A new methodological approach

Abstract: The main goal of this paper is to explore whether and how we might integrate real options analysis into scenario planning in order to overcome the limitations and enhance the benefits of both techniques. So far scholars have emphasized that the main advantages of scenarios consist in developing the learning and adaptive skills of organizations. We thus investigate how to develop further these learning skills. Our paper contributes to the strategic management literature in three ways. First, it illustrates a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 72 publications
0
20
0
1
Order By: Relevance
“…As described by Bowman (2015), this planning tool stimulates decision makers to develop and clarify the practical choices, policies, and actions that can be taken, as well as their consequences (Coates, 2000), and to enrich their portfolio of "possible strategic initiatives", thus leading to action ( Van der Heijden, 2004). Favato and Vecchiato (2016), in their research on the strategic role of scenario planning, show the benefits of scenarios on flexibility and adaptation, as they establish a learning process that improves strategic decisions. It enables them to test the robustness of plans of action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described by Bowman (2015), this planning tool stimulates decision makers to develop and clarify the practical choices, policies, and actions that can be taken, as well as their consequences (Coates, 2000), and to enrich their portfolio of "possible strategic initiatives", thus leading to action ( Van der Heijden, 2004). Favato and Vecchiato (2016), in their research on the strategic role of scenario planning, show the benefits of scenarios on flexibility and adaptation, as they establish a learning process that improves strategic decisions. It enables them to test the robustness of plans of action.…”
Section: Discussionmentioning
confidence: 99%
“…The strategies developed are tested against the set of assumptions about changes and environmental uncertainty. Favato and Vecchiato (2016), in their research on the strategic role of scenario planning, show the benefits of scenarios on flexibility and adaptation, as they establish a learning process that improves strategic decisions. As such, they enable us to continuously explore long-range opportunities and threats.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, research on real options has shown that this foresight technique provides an effective framework for the systematic generation and evaluation of alternative investment decisions (McGrath et al, ). We suggest that future research efforts focus on real options and, in particular, the combination of real options with scenarios as a valuable foresight approach that fosters the flexibility of managers’ mental models about future sources of competitive advantage (Favato & Vecchiato, ). In the automotive industry, the combined use of scenarios and real options should be aimed to reduce the risk of betting on the wrong future while still giving firms the opportunity to achieve first‐mover advantages.…”
Section: Foresight and Cognition In The Automotive Industry: Recommenmentioning
confidence: 99%
“…In order to assess the overall situation of the company, these values (Very bad, Bad, Acceptable, and Good) can be transformed into numeric values, for example (2,3,4,5), and use in computational models. Additionally, a manager can give weights to variables in the range prototype [0,1], where 0 is a negligible variable, and 1 is a very important variable.…”
Section: Fig 3 Example Of Values Transformationmentioning
confidence: 99%
“…Real options have been applied in practice to solve such issues as just described. In addition, they are treated as the risk management instruments used to assess financial risk of high-risk development projects as well as to influence the company's ability to continue as a going concern in the future [1][2].…”
Section: Introductionmentioning
confidence: 99%